The Influence Of Work Discipline, Work Environment, And Compensation On Employee Performance At Pt Citra Wijaya Teknik - Yolandita Ilona; Agtovia Frimayasa (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
The main objective of this study is to determine the effect of career development, work environment and work discipline on the performance of PT Memory employees. The objects in this study were employees of PT Memory in the production section of 53 respondents. Data collection was carried out using a questionnaire distribution method. By using a random sampling technique. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The results showed that career development had a positive and significant effect on employee performance, the work environment had no effect on employee performance, and work discipline had no effect on employee performance. But the test together that Career Development, Work Environment and Work Discipline have a significant influence.